Everybody Eats: Using Hunger Banquets to Teach about Issues of Global Hunger and Inequality. (April 2015) - Harris, Deborah A.; Harris, Whitney M.; Fondren, Kristi M.
Experiential and active learning exercises can benefit students in sociology courses, particularly, courses in which issues of inequality are central. In this paper, we describe using hunger banquets—an active learning exercise where participants are randomly stratified into three global classes and receive food based upon their class position—to enhance students' knowledge of global hunger and inequality. The nonprofit Oxfam America has made hunger banquets popular, but they are usually large public events. We provide ways of simplifying these exercises so that they can be conducted in sociology classrooms and incorporate sociological concepts. Quantitative and qualitative analysis of students' learning and engagement in three hunger banquets found that students had increases in perceived knowledge of the amount, severity, and causes of global hunger.